Climatic Assessment of Walls Inspired by Hierarchical (Hereditary) Structures in Nature - Leila sadat Hamidian Divkolaei; Seyyedeh Mahsa Bagheri (توسعه پایدار شهری)
Building walls are one of the main building components and elements that are considered in the topic of climate design. Ignoring and not paying attention to how the walls are structured can lead to significant energy wastage. In this article, it is intended to design a building wall sample inspired by nature (hierarchical diatom structure) and evaluate it in terms of energy consumption conditions. Nature, as the mother of man and all creatures and a source full of ideas, technology and all tested phenomena, can be a stable source for creating ideas and modeling it for humans in order to reduce the effects of various crises. It seems that the solution to all human crises, including crises and energy shortages, identity crisis, which appear in the form of various and fragmented identities, is all under the shelter of nature. According to the successful experiences of nature in the correct way of energy consumption, it seems that by observing and discovering nature in order to model a structure of it, can obtain acceptable results in energy consumption management. In this research, a wall with the help of Rhino software and Grass hoper plugin constructed, inspired by a type of diatoms - a structure of algae - has been designed and evaluated with the help of the software. In this research, the building wall in a temperate and humid climate has been evaluated with the help of Rhino software and Grasshoper plugin, inspired by a type of diatoms with the help of Ecotect Analysis 2010 software. The results of this research show that walls modeled by nature lose less heat in the cold seasons of the year and gain less heat in the hot seasons of the year compared to other conditions. Also, the thermal diagrams among the zones show that the greatest decrease in temperature in the hot seasons of the year among the zones is observed in the walls covered with the genetic pattern. This problem indicates that these walls act like a filter against the outside air. According to the climate studies of Babolsar city and the prevailing need for heating in this city, it seems that the use of shells modeled on nature will bring the temperature inside the space closer to the comfort temperature. Therefore, these walls will perform better in annual energy consumption. Also, the findings indicate that if biomimetic adaptive walls are used, the temperature inside the space will be close to comfort temperature in more hours of the year. It is obvious that by returning to nature and identifying the hidden patterns in it, we can take a step towards the stability and durability of buildings and pay attention to the protection of the ecosystem. The flexibility and adaptability of biomimetic models show how biological strategies and properties can enhance and improve performance in different environments, just as the organisms that inspire innovation are already well adapted to conditions on Earth. It is obvious that by returning to nature and identifying the hidden patterns in it, one can take a step towards the stability of buildings and preserving the ecosystem.